2020
DOI: 10.1111/ina.12765
|View full text |Cite
|
Sign up to set email alerts
|

Particulate matter emitted from ultrasonic humidifiers—Chemical composition and implication to indoor air

Abstract: Household humidification is widely practiced to combat dry indoor air. While the benefits of household humidification are widely perceived, its implications to the indoor air have not been critically appraised. In particular, ultrasonic humidifiers are known to generate fine particulate matter (PM). In this study, we first conducted laboratory experiments to investigate the size, quantity, and chemical composition of PM generated by an ultrasonic humidifier. The mass of PM generated showed a correlation with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 51 publications
0
31
0
1
Order By: Relevance
“…PM composition is an amalgamation of both local and distal environmental factors (Nääv et al, 2020), using nebulizers to aerosolize PM into the environment may have affected PM 2.5 composition in both exposed and control conditions. This may be particularly important since it has been shown that humidifiers increase the concentration of PM in direct correlation to the concentration of solutes and ions present in the water used (Lau et al, 2021). Further highlighting the need for investigations into how variability in PM 2.5 composition, climate, and delivery methods can contribute to the physiological post‐exposure effects.…”
Section: Discussionmentioning
confidence: 99%
“…PM composition is an amalgamation of both local and distal environmental factors (Nääv et al, 2020), using nebulizers to aerosolize PM into the environment may have affected PM 2.5 composition in both exposed and control conditions. This may be particularly important since it has been shown that humidifiers increase the concentration of PM in direct correlation to the concentration of solutes and ions present in the water used (Lau et al, 2021). Further highlighting the need for investigations into how variability in PM 2.5 composition, climate, and delivery methods can contribute to the physiological post‐exposure effects.…”
Section: Discussionmentioning
confidence: 99%
“…The air exchange rate coefficient was calculated to be 5.0 × 10 −4 s −1 , or 1.8 h −1 , based on the first‐order decay of CO 2 . This method is a common way to determine the air exchange rate in indoor spaces 10,13 …”
Section: Methodsmentioning
confidence: 99%
“…This method is a common way to determine the air exchange rate in indoor spaces. 10,13 The fog was generated by a commercially available AFM. It is portable and one of the popular models sold online.…”
Section: Generation Of Fog Aerosol In An Experimental Officementioning
confidence: 99%
See 1 more Smart Citation
“…For instance, typical human activities can generate substantial concentrations of airborne particles indoors relative to background concentrations. Examples of such activities include cooking and other forms of surface heating, incomplete combustion (e.g., candles and incense), vacuuming, and use of cleaning products, , ultrasonic essential oil diffusers, and humidifiers . In addition, nonsedentary activities (e.g., walking) can resuspend settled particles (dust). , …”
Section: Introductionmentioning
confidence: 99%